Acid Treatment Enables Suppression of Electron–Hole Recombination in Hematite for Photoelectrochemical Water Splitting. Issue 10 (5th February 2016) - Yang, Yi; Forster, Mark; Ling, Yichuan; Wang, Gongming; Zhai, Teng; Tong, Yexiang; Cowan, Alexander J.; Li, Yat
Abstract: We report a strategy for efficient suppression of electron–hole recombination in hematite photoanodes. Acid‐treated hematite showed a substantially enhanced photocurrent density compared to untreated samples. Electrochemical impedance spectroscopy studies revealed that the enhanced photocurrent is partly due to improved efficiency of charge separation. Transient absorption spectroscopic studies coupled to electrochemical measurements indicate that, in addition to improved bulk electrochemical properties, acid‐treated hematite has significantly decreased surface electron–hole recombination losses owing to a greater yield of the trapped photoelectrons being extracted to the external circuit. Abstract : A simple acid treatment method is reported to increase the photoelectrochemical activity of hematite photoanodes. The enhanced photocurrent was due to the combination of improved efficiency of charge separation and suppressed electron–hole recombination, resulting in a greater yield of trapped photoelectrons being extracted to the external circuit.